Mechanics in dehydration-induced leaf morphing behaviors - Guo, Kexin (Nanyang Technological University, 2024)
Plant leaf morphogenesis gives rise to a fascinating variety of shapes, with leaves exhibiting intriguing adaptive responses to changes in their environment. The remarkable ability of plant leaves to undergo shape-morphing in response to environmental cues has inspired the development of engineering machines and devices. While some typical shape changes in plants and their mechanical driving forces have been extensively studied, numerous unexplored behaviors and underlying mechanical principles still exist in nature. Understanding such phenomena not only offers insights into how plants overcome environmental challenges but also paves the way for innovative approaches in developing biomimetic structures and devices. This thesis focuses on three shape-morphing phenomena observed in plant leaves as passive responses to the strain mismatch caused by dehydration. The research findings indicate the significant influence of mechanics on the formation of leaf shapes.